The soluble ST2 levels in patients with depression and comorbid heart failure - A. Sikora; S. Fedorov; M. Vynnyk; M. Pustovoyt; O. Pityk; J. Bezuk (European Psychiatry, 2022)
Introduction Depression in HF has become a major issue as the burden of HF has continued to increase, and many studies have suggested poorer outcomes in HF patients reporting depression. The prevalence of major depression in HF is about 20–40 %, which is 4–5 % higher than in the normal population. Soluble ST2 is involved in multiple pathogenetic pathways including cardiac strain, inflammation, and myocardial necrosis with remodeling.